Rules-Based Accounting Standards and Litigation - Donelson, Dain C.; McInnis, John M.; Mergenthaler, Richard D. (The Accounting Review, 2012)
ABSTRACT Some claim that rules-based accounting standards shield firms from litigation, while others argue that violations of detailed rules give plaintiffs a “roadmap” to successful litigation. We inform this debate by investigating whether rules-based standards are associated with the incidence and outcome of securities class action litigation. Overall, our results suggest that rules-based standards are associated with a lower incidence of litigation but are not associated with litigation outcomes. These results are of interest in the debate regarding the switch from a more rules-based U.S. GAAP to a more principles-based IFRS. JEL Classifications: K22, K41, M41.